Pesticide watchers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Getting your horticultural produce to European markets involves more than wrapping and transporting it. One of the sets of criteria your fruits and vegetables have to meet is that they not only have to be free from pests but also have to comply with...